PAHs, elemental and organic carbons in a highway tunnel atmosphere and road dust: Discrimination of diesel and gasoline emissions. (August 2019) - Demir, Tuğçe; Yenisoy-Karakaş, Serpil; Karakaş, Duran
Abstract: Total suspended solid (TSP) samples were collected in the Bolu Mountain Tunnel located on the highway in the axis of Edirne-Istanbul-Ankara in Turkey, by using PUF samplers. The concentrations of elemental and organic carbons (EC and OC) and particulate and gas phase priority pollutant (US-EPA) PAH compounds were determined at the entrance and the exit of the tunnel. Two sampling surveys were performed for summer and winter seasons in order to examine the seasonal changes of emissions. The OC peaks were associated with the sum concentrations of PAH compounds with respect to their boiling points. The fractions of OC1, EC3 and EC4 dominated in the tunnel particulate samples and OC4 and EC2 fractions formed the largest fraction of the particulate carbonaceous part of road dust. The results indicated that the predominant species in the particulate phase were the low-molecular weight (LMW) PAHs and low OC/EC ratios which indicated the dominance of the usage of diesel fuel in the vehicles. The highest emission factors (μg/vehicle −1 km −1 ) were observed for PhA, Ant and Py in summer, and for PhA, Fl and Py in winter seasons. Due to the strong influence of diesel-fueled vehicle emissions, higher correlations were observed between the fleet compositions of heavy duty vehicles (HDV) and obtained emission factors of OC, EC and PAHs than the correlations of light duty vehicles (LDV) in tunnel atmosphere for both summer and winter season. It was determined that PAHs potential risk for the health of the tunnel workers were significant. Highlights: OC1, EC3 and EC4 fractions dominated in the tunnel atmosphere. The dominance of LMW PAHs and OC/EC-PAH ratios indicated the diesel emissions. Three OC peaks were highly related with the sum of selected PAH concentrations. The high correlations were found between combustion-related PAHs and EC. The reference values were obtained for Turkish fleet.